2005
DOI: 10.2116/analsci.21.1457
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Discrimination of Fatty Acid Composition in Fats and Oils by Electrospray Ionization Mass Spectrometry

Abstract: Fatty acids in 42 types of saponified vegetable and animal oils were analyzed by electrospray ionization mass spectrometry (ESI-MS) for the development of their rapid discrimination. The compositions were compared with those analyzed by gas chromatography-mass spectrometry (GC-MS), a more conventional method used in the discrimination of fats and oils. Fatty acids extracted with 2-propanol were detected as deprotonated molecular ions ([M-H] -) in the ESI-MS spectra of the negative-ion mode. The composition obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 23 publications
1
14
0
2
Order By: Relevance
“…In countries like New Zealand [17], Costa Rica [7] and Pakistan [4] some unusual fatty acids in vegetable oils as 15:0 and 17:0 were found in margarines [4]. This last fatty acid (17:0) was also found in some margarines marketed in Mexico (present work), it could be due to the incorporation of animal fats in margarine production since almost all animal fats contain 17:0 fatty acid [18]. Table 6 also shows that in Mexico as well as in Turkey [19,20], Pakistan [4,21], Costa Rica [7] and New Zealand [17] is common to use palm or coconut oil in margarines indicated by the high content of 16:0 found, with values as high as 44% of total fatty acids.…”
Section: Resultssupporting
confidence: 60%
“…In countries like New Zealand [17], Costa Rica [7] and Pakistan [4] some unusual fatty acids in vegetable oils as 15:0 and 17:0 were found in margarines [4]. This last fatty acid (17:0) was also found in some margarines marketed in Mexico (present work), it could be due to the incorporation of animal fats in margarine production since almost all animal fats contain 17:0 fatty acid [18]. Table 6 also shows that in Mexico as well as in Turkey [19,20], Pakistan [4,21], Costa Rica [7] and New Zealand [17] is common to use palm or coconut oil in margarines indicated by the high content of 16:0 found, with values as high as 44% of total fatty acids.…”
Section: Resultssupporting
confidence: 60%
“…An overview of the different instrumental techniques used for the analysis of plant, fish and marine mammal oils in studies where the terms discrimination, adulteration, classification, profiling, differentiation, authentication or characterization have been a vital and important component of the various studies revealed that the focus has been on plant oils [341] by using mainly different types of chromatography, infrared absorption, nuclear magnetic resonance and mass spectrometry techniques. Studies on fish and marine mammal oils are scarce [4147].…”
Section: Introductionmentioning
confidence: 99%
“…An overview of the different instrumental techniques used for the analysis of plant, fish and marine mammal oils in studies where the terms discrimination, adulteration, classification, profiling, differentiation, authentication or characterization have been a vital and important component of the various studies revealed that the focus has been on plant oils [341] by using mainly different types of chromatography, infrared absorption, nuclear magnetic resonance and mass spectrometry techniques. Studies on fish and marine mammal oils are scarce [4147]. In addition, the literature overview revealed that multivariate techniques, especially principal component analysis (PCA), were the preferred data analysis approaches used in the majority of these oil discrimination studies [3, 5, 8, 1014, 16, 17, 1922, 2528, 30, 3438, 40, 4244, 46, 47] and that the potential of simple techniques such as gas chromatography (GC) has not been explored yet in the discrimination of fish and marine mammal oils by using the conventional fatty acid methyl ester (FAME) profiles.…”
Section: Introductionmentioning
confidence: 99%
“…Komposisi asam palmitat selalu ada dalam berbagai minyak dan lemak, namun besar kecilnya berbeda antara satu sumber dengan lainnya, misalnya; minyak sawit 43,1 %, minyak kelapa 9,8 %, minyak bunga matahari 6,08 %, minyak biji kapas 20-25 %, mentega 24-26 %, lemak babi 28-30 %, lemak unggas 24-32 %, pelumas 23-24 %, minyak zaitun 9,10 %, minyak jagung 8-12%, minyak kedelai 6-10 %, dan minyak kacang tanah 8-9 % serta minyak canola 4-5 % (Knothe et al, 1997;Kurata et al, 2005).…”
Section: Introductionunclassified